Address given... at the Annual Luncheon Meeting of the Employers Federation of Barbados - Venner, K. Dwight (Eastern Caribbean Central Bank BasseterreKN, 1993)
Focuses on global economic trends and developments and their effect on Caribbean economies. Makes suggestions for overcoming the difficulties.